Literature Review and Integration of Biomedical and Psychodynamic Conceptualizations of ADHD| Toward a Theoretical Synthesis of a Complex Multifactorial Syndrome - Belitski, Maya Sophia (California Institute of Integral Studies, 2017)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a childhood-onset neurodevelopmental syndrome associated with pervasive impairment in social, emotional, and cognitive functioning and development. The skyrocketing prevalence, controversial pharmaceutical treatment, and mounting public cost associated with ADHD has stimulated an explosion of research in increasingly specialized scientific domains, establishing a multifactorial etiology based in the dynamic transaction of genetic, neuromolecular, neurocognitive, and socioenvironmental mechanisms. Most contemporary biomedical research on ADHD has remained siloed in competing etiological models that independently account for this syndrome, yet fail to translate and integrate field-specific advances in knowledge across disciplines and persist in the outmoded tradition attempting to establish a putative single, or core, underlying cause. As a consequence, the current available treatment offered for ADHD has remained almost exclusively limited to the controversial and often contraindicated reliance on potentially dangerous psychostimulant drugs. The dearth of interdisciplinary collaboration and translational knowledge has significantly inhibited the development of a unifying diagnostic conceptualization of ADHD that is necessary to guide the study and implementation of more efficacious developmentally informed psychosocial interventions for ADHD. This integrated literature review was undertaken to achieve greater consilience between the preeminent scientific clinical models proposed to account for the pathophysiology underlying ADHD. A detailed review of biomedical empirical investigation and psychoanalytic clinical theory revealed two distinct, yet highly complementary etiological models of ADHD. In particular, this literature review elucidates how adverse experiences encountered in early childhood, such as insecure attachment with primary caregivers, may pose a disproportionate risk to children with a biogenetic susceptibility to ADHD. Based on this review, it is proposed that a multifactorial analysis of the contemporary biopsychosocial perspectives on ADHD have relevance to improving clinical efforts to more holistically conceptualize, prevent, and treat this complex and pernicious syndrome. If patients and clinicians can share a more multidimensional understanding of what developmental factors are implicated in the risks associated with the causal etiology and maintenance of ADHD, they may be able to act as more agentic collaborators in addressing and treating problematic symptoms associated with this condition.